Banco de Oro's PC-based system a key for quality customer service - Daradar, Maricon D.
Undaunted by the prevailing milieu, re-engineering became Banco de Oro's strategic focus, as processed and procedures were redesigned and simplified to deliver quality service and added customer convenience. Pilot branchez were redodeled, aimed at optimizing customer contact, emphasiizing marketing and sales, and clustering bank office functions. As part of the branch reengineering of BDO, new accounts transactions were also restructured to provide quality customer service to the clients through the use of a PC-based systems. This study analyzes and compares Banco de Oro's new accounts performance using the old system vis-a-vis the new PC based system. based from the results of the study, the PC based System has improved Banco de Oro's customer service. Their goal for a better service has been realized. The new account clerks on the other hand are quite happy and contented with their job and still hopeful for the full effect of the reengineering of the old banking system of Banco de oro. The devaluation of peso also affected the workforce and transactions of Banco de Oro especially the Iloilo-Valeria branch since the bank is well known for its high buying exchange rate. Consequently, the voluminous increased transactions in foreign exchange greatly affected the customer service catering to other products and services of Banco de Oro. Moreover, the total result of this researcch helped the management to see the effect of reengineering. The result also indicated thet even though the PC Based System improved the service time, the voluminous increased transactions in foreign exchange can still disrupt the customer service. Thus, the management should be aware of this problem since ignorance of such can destroy the whole service time of other products and services. A good suggestion is to have an additional new account clerks (additional of 2 new accounts) or have a specialized teller that could handle all foreign exchange particularly accepting, identifying (original or counterfeit), and at the same time give payments to purchases and sale of dollars.